Praktik Pengelolaan Limbah Popok Sekali Pakai (Poksa) - Septi Ariadi (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
This paper contains a theoretical explanation of the practice of managing disposable diaper (popok sekali pakai/poksa) waste. This explanation uses the structuration theory point of view from Anthony Giddens. The selection of the structuration theory is based on the consideration that disposable diaper waste is one of the environmental problems experienced by modern society. Disposable diaper waste is not only a problem in one particular area, but is a global problem. In addition, the main problems in the practice of managing disposable diaper waste are in accordance with several concepts proposed by the structuration theory. The practice of disposable diaper waste management in structuration theory is seen as related to the formation of scenarios about the practice. The advice that can be given is to encourage experts in various fields related to disposable diaper waste to create the same narrative and scenario about the impact of disposable diaper waste and how to manage it for environmental sustainability. However, this theory does not provide an explanation of the role of agencies and the state to solve environmental problems in general and the waste of disposable diapers in particular. This theory also does not emphasize the medium of internalizing the value of the structure to agents. The use of other theories can be considered to explain this problem, namely the theory of social practice from Piere Bourdieu.